Qatar's Role in Promoting International Peace through Interfaith Dialogue: A Case Study of the Doha International Center for Interfaith Dialogue - Hazaymeh, Omar (MultiTech Publisher, 2024)
This paper explores the significant role of Qatar in promoting international peace and conflict resolution through its dedicated efforts in fostering interfaith dialogue, with a focus on the Doha International Center for Interfaith Dialogue (DICID). Qatar's diplomatic strategy emphasizes the importance of dialogue and negotiation, positioning the nation as a neutral mediator in global conflicts. The DICID, established in 2007, exemplifies Qatar's commitment to building mutual understanding and respect among diverse religious communities. Through its wide range of activities, including international conferences, workshops, community outreach, youth engagement, educational programs, and cultural exchanges, DICID has made substantial contributions to fostering interfaith dialogue. The center's efforts have had a significant impact on promoting mutual understanding, influencing policies, supporting conflict resolution, and shaping global discourses on religious tolerance. By building networks and partnerships, DICID enhances social cohesion and stability, promoting a culture of peace that transcends religious and cultural boundaries. The paper highlights how DICID's initiatives align with Qatar's broader diplomatic goals and examines the tangible outcomes of these efforts in fostering global peace. It underscores the importance of interfaith dialogue as a critical tool for conflict resolution and emphasizes Qatar's pivotal role in promoting a more peaceful and inclusive world. Through this analysis, the paper contributes to a deeper understanding of the vital role that interfaith dialogue plays in international diplomacy and peace-building.